APPLICATION OF SCIENTIFIC INQUIRY LEARNING MODEL TO IMPROVE MOTIVATION AND LEARNING OUTCOMES OF CLASS X STUDENTS IN VIRUS MATERIALS IN SMA NEGERI 11 BANDA ACEH - Ariannisa Ramadhanti; Muhibbuddin Muhibbuddin; Andi Ulfa Tenri Pada; Asiah Asiah; Supriatno Supriatno (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Student learning motivation is classified as less optimal due to several reasons, namely students tend to participate less during question and answer activities from their teacher and pay less attention to the teacher when delivering material in the learning process. The purpose of this research is to find out the application of the Scientific Inquiry Learning Model in increasing motivation and student learning outcomes on virus material. This study uses a pretest-posttest control group design experimental method. The parameters used are learning motivation and student learning outcomes collected through pretest and posttest. The data obtained were then tabulated and analyzed using the N-Gain formula to find out the improvement in learning outcomes. Next, a statistical analysis was carried out in the form of the Independent sample t-test and the Mann-Whitney test to determine differences in motivation scores and learning outcomes in the experimental and control class students. For learning motivation, the data obtained were also analyzed by the percentage of scores per indicator to determine its categorization. The results obtained for Independent sample t-test of the average learning motivation, obtained tcount = 5.07 ttable = 4.1. For categorization, the experimental class received an average of "very good", "good", and "good enough" categorizations. As for the learning outcomes obtained Mann-Whitney test results namely Zcount = 5.71 Ztable = 1.96 so it can be concluded that the Scientific Inquiry learning model can increase student motivation and can improve student learning outcomes on virus material.Motivasi belajar siswa tergolong kurang Optimal dikarenakan beberapa alasan yaitu siswa cenderung kurang berpartisipasi saat kegiatan tanya jawab dari gurunya serta kurang memperhatikan gurunya saat penyampaian materi dalam proses pembelajaran. Pelaksanaan riset bertujuan mengetahui penerapan Model Pembelajaran Scientific Inquiry dalam peningkatan motivasi serta hasil belajar siswa pada materi virus. Risetini menggunakan metode eksperimen berdesain Pretest-Posttest Control Group. Parameter yang digunakan yaitu motivasi belajar serta hasil belajar siswa yang dikumpulkan melalui pretest dan posttest. Data yang diperoleh selanjutnya ditabulasi dan dianalisis dengan rumus N-Gain untuk mengetahui peningkatan skor. Selanjutnya, dilakukan analisis statistika berupa uji Independent sample t-test dan uji Mann-Whitney untuk mengetahui perbedaan skor motivasi dan hasil belajar pada siswa kelas eksperimen dan kelas kontrol. Untuk motivasi belajar, data yang diperoleh juga dianalisis persentase skor per indikator untuk diketahui kategorisasinya. Hasil riset uji Independent sample t-test untuk motivasi belajar, diperoleh thitung = 5,07 ttabel = 4,1. Untuk kategorisasi, kelas ekperimen mendapat rata-rata kategori “sangat baik”, “baik”, dan “cukup baik”. Sedangkan untuk hasil belajar diperoleh hasil uji Mann-Whitney yaitu Zhitung = 5,71 Ztabel = 1,96 sehingga dapat disimpulkan bahwa model pembelajaran Scientific Inquiry dapat meningkatkan motivasi belajar siswa serta dapat meningkatkan hasil belajar siswa pada materi virus.